Charge screening-controlled Verwey phase transition in Fe3O4/SrTiO3 heterostructure. (21st February 2018) - Ji, H; Wang, Y G; Li, Y
Abstract: Despite intensive investigations into the Verwey phase transition of Fe3 O4 over half a century, the mechanism of this phase transition remains controversial and needs further research. In this work, we build the Fe3 O4 /SrTiO3 multiferroic heterostructure and investigate the temperature dependence of its saturation magnetization under various electric fields. It is found that the charge-screening effect not only influences the magnetization but also induces the temperature of the Verwey phase transition shifting ~13 K. It suggests that the Verwey phase transition has certain correlations with the electron distribution and the change of the number of minority spin electrons in the trimerons plays a dominant role in the temperature shift of the phase transition.